Financial Decision, Innovation, Profitability and Company Value: Study on Manufacturing Company Listed in Indonesian Stock Exchange - Mursalim, Mursalim; ., Nur Alamzah; ., Abdullah Sanusi (Information Management and Business Review, 2015)
This study aims to describe the relationship between financial decisions, innovation, enterprise profitability and the value of the company. Based on the research objectives, this research is a causality research. The data used are secondary data for a 5-years period, obtained through several sources such as Indonesian Capital Market Directory (ICMD) and the websites of 22 companies. The results show that (1) Investment decision affects company profitability positively and significantly, (2) Investment decision affects company value positively and significantly, (3) Capital structure affects company profitability positively and significantly, (4) Capital structure affects company value positively and significantly, (5) Dividend policy affects company profitability positively and significantly, (6) Dividend policy does not affect company value, (7) Innovation affects company profitability positively and significantly, (8) Innovation affects company value positively and significantly, and (9) Profitability affects company value positively and significantly.